Cathepsin K in the immunohistochemical diagnosis of melanocytic lesions - Rao, Qiu (e-Century Publishing Corporation, 2014)
Recent studies have demonstrated that cathepsin K seems to be a powerful marker in identifying the microphthalmia associated transcription factor (MITF) family tumors such as renal perivascular epithelioid cell neoplasms (PEComas), alveolar soft part sarcoma, and translocation-associated renal cell carcinomas. However, the expression of cathepsin K in melanocytic lesions has not been well characterized. Our aim was to investigate the expression of cathepsin K in a wide histological spectrum of melanocytic lesions and to evaluate its potential diagnostic and molecular target therapy usefulness in comparison with other commonly used markers. 143 consecutive melanocytic lesions were selected for study including 56 primary malignant melanomas, 62 metastatic melanomas, and 25 benign nevi (16 intradermal melanocytic nevi and 9 compound melanocytic nevi). 107 of the 118 (91%) primary and metastatic melanomas displayed a high percentage of cells with moderately to strongly positive reactions for cathepsin K (mean 82%; range 0-95%). MITF, HMB45, Melan-A, and S100 were expressed in 85, 76, 78 and 96% of cases, respectively, with various percentages of positive cells (mean, 63, 49, 55 and 86%; range 0-90, 0-80, 0-90 and 0-95%). Among the benign nevi, cathepsin K, MITF, HMB45, Melan-A, and S100 were expressed in 88, 80, 36, 68 and 100% of cases, respectively. Cathepsin K appears to be consistently and strongly expressed in melanocytic lesions and valuable in distinguishing malignant melanomas from the majority of human cancers.